English in medicine : a course in communication skills - Glendinning, Eric H; Holmström, Beverly A. S (Cambridge University Press, 1987)
English in Medicine is a new course which develops the English language skills required by foreign medical personnel for successful communication in their work. The book is organised into seven units which follow the stages of patient management from initial presentation to treatment: Taking a History 1 & 2, Examinations, Specialist Examinations, Investigations, Diagnosis, Treatment. All the material has been produced in close co-operation with medical experts and is based on real case studies, It includes taped interviews, authentic documents, practice material for the PLAB examination, a list of common medical abbreviations, key language items, and a key to the exercises.
Keywords: lékařství; angličtina; všeobecná příručková díla a encyklopedie; Terminology as Topic; lingvistika; lingvistika, lékařská terminologie; Linguistics; terminologie jako téma